Potentiostatic and pulsed electrodeposition of zinc selenide thin film - Ng, Sook Mey (2013)
Zinc selenide attracts a lot of attention due to its wide potential applications in photovoltaic and optoelectronic devices, photodiodes, superionic conductors and sensors. Among all the techniques to synthesize ZnSe, electrodeposition is the simplest and the most cost-effective as well as it enables low temperature growth. However, in the previous work the influence of electrodeposition parameters in producing stoichiometric ZnSe and the effect on the photocurrent and optical properties were not studied in detail. In this work, ZnSe films were electrodeposited to produce stoichiometric films on ITO and their structural, optical and photoeelctrochemical properties were studied. The effect of varying selenium concentrations on the stoichiometric and optical properties of the films was also investigated. The deposition potential range for synthesizing zinc selenide films was determined using cyclic voltammetry. Film produced was characterized using X-ray Diffractometry (XRD) to determine the crystal structural, Linear Sweep Photovoltammetry Test (LSPV) to evaluate the photosensitivity to light, Scanning Electron Microscopy (SEM) to examine on the film morphology and High Surface Profiler to determine the film thickness. Optical band gap and the transition type of the films were determined using data obtained from UV-Vis Spectrophotometer. The electronic properties of ZnSe thin films were investigated by photoluminescence (PL) technique. Potentiostatic eletrodeposition was carried out at different deposition potential, selenious acid concentrations, deposition time, bath temperatures and annealing temperatures. The XRD pattern showed that both as-deposited and annealed ZnSe films obtained from the increases deposition potential from -1.0 V to -0.6 V were polycrystalline with cubic phase for all selenious acid concentrations from 4 mM to 10 mM. Increasing deposition time from 1 hour to 3 hours and bath temperature from 27 °C to 80 °C, however, favors the growth of selenium rich films. Zinc selenide forms better deposit in acidic condition with optimum pH of 2.00. Pulse electrodeposition was carried out by varying the cathodic pulse potential and duty cycles of 30 %, 50 %, 70 % and 90 %. The photocurrent response of the deposit increases with increasing duty cycles. However, the deposits showed poor photocurrent compared to samples deposited by potentiostatic technique. The ZnSe films preparative parameters of both techniques were optimized based on their photosensitivity and stoichiometry of the films. All films exhibit good photoresponse towards white light with p-type semiconducting character in photoelectrochemical test. Calcination at temperature above 200 °C reduced the selenium content and improved the stoichiometry of the films. The film showed direct optical transition with the band gap of 2.65 eV. The photoluminescence studies the fundamental electronic properties of ZnSe. Stoichiometric ZnSe films with different thicknesses were illuminated at different excitation wavelengths. Emission peak became more intense and narrow as the films excited to higher excitation wavelength. The ZnSe emission spectra obtained at a wavelength range is associated to the blue region which makes it suitable for fabrication of light emitting devices operating in the blue-green light and short-wavelength devices.